ALK-Positive Histiocytosis: A Case Report and Literature Review - Omar Issa JABER; Doa' AL JARRAH; Mohammad HIASAT; Maysa AL HUSSAINI (Federation of Turkish Pathology Societies, 2021)
ALK positive histiocytosis is a relatively new histiocytic proliferation disease with a characteristic gene translocation involving fusion of the ALK gene with different partners, mostly KIF5B. We report a case of ALK-positive histiocytosis with literature review. A 27-year-old male patient presented mainly with progressive lower limb weakness. Imaging studies showed an intradural extramedullary enhancing lesion at the L3 level. A 1.5 cm mass was excised from the sensory nerve root in the filum terminale at the level of L3. Histologic examination showed infiltration of the nerve by numerous histiocytes with moderate to abundant eosinophilic to clear-foamy and variably-vacuolated cytoplasm with irregular-to-smooth contoured nuclei. The histiocytes were positive for CD68 and ALK1 and negative for S100 and CD1a. KIF5B-ALK fusion was detected by real time-polymerase chain reaction. The patient is asymptomatic nine months after surgical excision. This is the first reported localized case occurring in the nerve root of an adult patient, thus expanding the clinical manifestations of this disease. An integrated histological, immunohistochemical and molecular approach is recommended for diagnosis. We recommend performing ALK1 immunohistochemical stain on all histiocytosis cases to increase awareness and detection of this newly described entity.